VALUASI EKONOMI MENGGUNAKAN METODE TRAVEL COST PADA TAMAN WISATA ALAM PUNTI KAYU PALEMBANG - Muhammad Subardin (Department of Development Economics, Universitas Sriwijaya, 2011)
The aim of these study are to estimate the demand similarity of recreation benefit in Taman Wisata Alam Punti Kayu based on travel cost method. The similarity estimate model of recreation demand based on travel cost method that is : Y = 118,323 – 1,419 (x). These model is very significant (P = 0,005) with coefficient of determination equal to 81,5 percent. The result of this research show that development of Taman Wisata Alam Punti Kayu give a positive impact for consumers welfare. Also from this research, should know that consumer surplus equal to Rp.16.937.214,25/year. Keywords: travel cost method, consumer surplus